Kirenol, darutoside and hesperidin contribute to the anti-inflammatory and analgesic activities of Siegesbeckia pubescens makino by inhibiting COX-2 expression and inflammatory cell infiltration. (25th March 2021) - Li, Yu-Sang; Zhang, Jian; Tian, Gui-Hua; Shang, Hong-Cai; Tang, He-Bin
Abstract: Ethnopharmacological relevance: The Chinese traditional medicine of Siegesbeckia pubescens Makino (SM), which has the effect of healing rheumatism and promoting joint health, is often used to treat rheumatoid arthritis and ischemic stroke. Aim of the study: To clarify the mechanisms underlying the anti-inflammatory and analgesic influence of active components in the ethanol extract of Siegesbeckia pubescens Makino (ESM). Materials and methods: The active ingredients in the ESM were identified practicing high-performance liquid chromatography-diode array detection (HPLC-DAD). Four models including xylene-induced ear oedema, complete Freund's adjuvant (CFA)-induced hind paw oedema, acetic acid-induced pain writhing and lipopolysaccharide (LPS)-induced RAW264.7 cell migration, were used to clarify the anti-inflammatory and analgesic mechanisms of the active ingredients in the ESM. Results: (1) Three active ingredients of kirenol, darutoside and hesperidin were identified in the ESM, with relative proportion of 0.6%, 0.2% and 0.01%, respectively; hesperidin was reported for the first time in the ESM. (2) Both the ESM and its active ingredients could effectively alleviate the degree of swelling of the auricle and toes, increase the threshold of heat pain, decrease the overexpression of inflammatory protein cyclooxygenase-2 (COX-2) in the skin tissue of the tested parts of the toes, and reduce the number of writhes induced by acetic acid in mice. (3) ESM and its active ingredients also dose-dependently inhibited the migration of RAW264.7 cells. Conclusions: ESM and its active ingredients can effectively attenuate the expression of inflammatory factors induced by chemical inflammation, prevent the infiltration of inflammatory cells, and exert good anti-inflammatory and antinociceptive activities. Graphical abstract: Image 1 Highlights: The ESM has good anti-inflammatory and antinociceptive activities. Six ingredients with high content in the ESM were identified by HPLC-DAD. Three ingredients (kirenol, darutoside and hesperidin) were responsible for the anti-inflammatory and antinociceptive effects through inhibiting COX-2 protein expression.